Earnings Management in Malaysian Companies during the Global Financial Crisis and the Coincidental Effect of IFRS Adoption - Abdullah Mohammed Ayedh; A. H. Fatima; Muslim Har Sani Mohammad (Australasian Accounting, Business and Finance Journal, 2019)
Purpose: This research examines earnings management (EM) behavior during the 2008 financial crisis in Malaysia. Both magnitude and direction of EM are studied and compared with EM during the pre-crisis period. In the case of Malaysia, the Malaysian Accounting Standards Board (MASB) adopted the international accounting standards, i.e. the International Financial Reporting Standards (IFRS) just two years prior to the crisis period. These standards could have some influence on EM during the global financial crisis period in Malaysia, thus are also taken into consideration in this study. Methodology: Data were collected from the Bloomberg database, and the proxy for EM was discretionary accruals (DA), which were measured using two models, namely the modified Jones model by Dechow et al. (1995) and the modified Jones model by Kothari et al. (2005). Findings: The empirical findings of paired-sample T-tests for 1,189 firm-years revealed that EM practices in the Malaysian companies were income decreasing during the crisis period (2008 and 2009), compared to the pre-crisis period (2005 and 2006) when the practices were income-increasing. The findings of this study are consistent with big bath theory. Furthermore, simple multivariate regressions support the findings that EM is significantly more negative or less positive during the crisis period. Nevertheless, the adoption of IFRS seems to suggest some deterring influence on EM practices of Malaysian companies. Research Limitation: The limitation of this study is that it uses rudimentary measures to proxy crisis period and IFRS in the regressions. Moreover, this study includes only one control variable (company size). Practical implication: the findings of this study would inspire more research on EM during abnormal periods, such as a financial crisis period, whilst taking accounting regulation into consideration, particularly in Asian countries. In addition, the policy makers might give more attention to ensure the enhancement of the adherence of IFRS adoption. Originality: The paper addressed a practical issue of EM during crisis period using two different proxies. In addition, the paper applied the integrated variable CriIFRS, which reflects the crisis period, taking into consideration IFRS adoption. Albeit preliminary, this is considered the main originality and novelty of the current study.
Keywords: Earnings management; Financial crisis; accounting standards; Malaysia